Caso de estudio: IOI’S global challenge: moving up the palm oil value chain - Caballero Oquendo, Patricia Jimena (2019)
The present case study analyzes the company IOI Corporation Berhard, an Asian family business founded in the 80s, which is mainly engaged in palm plantation and the production of palm oil and derivatives. This study presents the current situation of the company, as well as the factors that allowed them to grow to a mini multinational and its strategy for the future. The analysis of the company will be carried out according to the following areas: market intelligence, international marketing, global strategic management, international logistics and international financing of the company For the analysis and development of the case study, methodologies such as matrices, ranking of factors and financial ratios were used, primary and secondary sources were also consulted to obtain more information. The purpose of the analysis is to determine if it is convenient for the company to make the proposed growth proposal. After performing the analysis, it was obtained as a result, that the company despite having a wide variety of products, presence in different countries and growing, has a high leverage and a low profit margin, due to different factors and to being in an industry with high risk and volatile